Experiment on of nozzle flow with sudden expansion at Mach 1.1 - Faheem, Mohammad; Kareem Ullah, Mohammad; Aabid, Abdul; Mokashi, Imran; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This present study discusses the outcome of the experimental investigations, and the efficacy of the tiny jets used to regulate the base pressure as well as the wall pressure in suddenly expanded flow. The control mechanism as tiny jets having a cross-section of 1 mm diameter was employed as the base pressure regulator at the exit periphery of the nozzle. The experiments were carried out to investigate and record the flow field at the rear end of the separated flow region for area ratio 4.84. Four tiny jets were placed at a distance of 6.5 mm away from the primary jet coming from the nozzle exit at ninety degrees apart, and the tiny control jets were flowing at sonic Mach number. The actual Mach number of the main jet was 1.1. The experimentation was accomplished at a different level of expansion (i. e., NPR = 3, 5, 7, 9, and 11) and the L/D ratio considered was from 10 to 1. This study mainly focuses on the development of the flow in the suddenly expanded duct, nature of the flow in the duct, and the impact of the Control on the wall pressure and the magnitude of the pressure along the duct. The wall pressure in the smooth duct is not unfavorably influenced by the control jets.